أساليب علم البيان البلاغي في سورة النبأ والنازعات: Methods of rhetorical statement in Surah An-Naba and An- Nazi’at - Faiz Ur Rehman; Dr. Ahmad Saeed Jan (Al Manhal Research Journal, 2023)
In the Holy Qur'an, Allah Almighty has poured out a great river of eloquence and power. His eloquence are evident from every word and every verse. For the sake of brevity, Deem has limited himself only to the rhetoric of Surat-Al-.Naba And in Surat- Al- Naziaat, out of the three arts of eloquence, i.e. knowledge - knowledge of meanings - knowledge of rhetoric and knowledge of innovation, only knowledge of rhetoric has been written. See below. The title of this paper is: Asalib al- Bayan al- Balaghi fi Surat An-Naba and An- Naziaat. As a result of research and investigation in this Surah, we had to write the following style of narration. 1-The eloquent analogy(altashbih albaligh) 2- Sensory analogy from both sides(altashbih alhisiyu min aljanibayn) 3-Simile representation( altashbih al tamthil) 4 -The analogy is rational for both sides(altashabih alaqliyu altarafayn) 5-Implicit similarity (altashabuyh aldimniu) 6 – A metaphor is a statement(alistiearat tisiruyhayah) 8 –The metaphor sent (almjazalmursal) 9- Mentalmetaphor ( almujazalaqlay) 10-Euphemism.(Al-Kinayah)